Bioinformatics and Internet: New Paradigm to Disciplines and Information Technology - Kanaujia, Shiva (Journal of Information and Knowledge, 2014)
The paper deals with the Bioinformatics and Internet. It introduces Bioinformatics and leads to Internet and its relation with Bioinformatics. Further discusses the various facilities, services provided by Internet for Bioinformatics. It further mentions required resources. Explains the links available on Internet, various products and services, involvement of private firms. It highlights some aspects related with techniques and tools for Bioinformatics on Internet. Explains some searching methods and role of library and information centres regarding Bioinformatics and Internet. Concludes with the idea that shows the importance of Bioinformatics on Internet